2014
DOI: 10.1007/s11227-014-1201-2
|View full text |Cite
|
Sign up to set email alerts
|

High performance lattice reduction on heterogeneous computing platform

Abstract: Jozsa, CM.; Domene Oltra, F.; Vidal Maciá, AM.; Piñero Sipán, MG.; González Salvador, A. (2014). High performance lattice reduction on heterogeneous computing platform. Journal of Supercomputing. 70(2):772-785. doi:10.1007/s11227-014-1201-2. Abstract The lattice reduction (LR) technique has become very important in many engineering fields. However, its high complexity makes difficult its use in real-time applications, especially in applications that deal with large matrices. As a solution, the Modified Block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Up until now, there is substantial work on computing platforms with tens of CPU cores e.g. [9], [13], [30], or, alternatively, solely on GPUs, but there is no work on CPU+GPU platforms, except for building blocks for attacks rather than attacks themselves [23] or attacks that can be broken down into many instances of the same attack [25], which is typically not the case with most attacks.…”
Section: A Preparing For the Post-quantum Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Up until now, there is substantial work on computing platforms with tens of CPU cores e.g. [9], [13], [30], or, alternatively, solely on GPUs, but there is no work on CPU+GPU platforms, except for building blocks for attacks rather than attacks themselves [23] or attacks that can be broken down into many instances of the same attack [25], which is typically not the case with most attacks.…”
Section: A Preparing For the Post-quantum Eramentioning
confidence: 99%
“…The second paper, published in 2014, implements a relaxed version of LLL, called ''cost-reduced MB-LLL'' or CR-MB-LLL, a lattice reduction algorithm, on heterogeneous systems [23]. The authors showed that the heterogeneous implementation of the CR-MB-LLL algorithm performs better than the multi-threaded version for CPUs, if large matrices (i.e.…”
Section: B Related Workmentioning
confidence: 99%